PI3K Signaling in Dendritic Cells Aggravates DSS-Induced Colitis - Kuttke, Mario; Hromadová, Dominika; Yildirim, Ceren; Brunner, Julia S.; Vogel, Andrea; Paar, Hannah; Peters, Sophie; Weber, Maria; Hofmann, Melanie; Kerndl, Martina; Kieler, Markus; Datler, Hannes; et al. (Frontiers in Immunology, 2022)
Aberrant innate immune responses to the gut microbiota are causally involved in the pathogenesis of inflammatory bowel diseases (IBD). The exact triggers and main signaling pathways activating innate immune cells and how they modulate adaptive immunity in IBD is still not completely understood. Here, we report that the PI3K/PTEN signaling pathway in dendritic cells enhances IL-6 production in a model of DSS-induced colitis. This results in exacerbated Th1 cell responses and increased mortality in DC-specific PTEN knockout (PTENΔDC) animals. Depletion of the gut microbiota using antibiotics as well as blocking IL-6R signaling rescued mortality in PTENΔDC mice, whereas adoptive transfer of Flt3L-derived PTEN-/- DCs into WT recipients exacerbated DSS-induced colitis and increased mortality. Taken together, we show that the PI3K signaling pathway in dendritic cells contributes to disease pathology by promoting IL-6 mediated Th1 responses.